Kajian Hadis Hukum Bersandar Dan Tidur-Tiduran Di Dalam Masjid Dalam Kitab Dhoif Al-Adab Al-Mufrod - Sampara Palili (Qolamuna : Jurnal Studi Islam, 2019)
This article discusses the 159th Hadith in the Book of Dhoif al-Adab al-Mufrod Imam al-Bukhari Karya Syeh Nasaruddin Al-Bani. This hadith discusses the law of leaning and lying in the mosque. The results showed that this hadith was issued by eight Mukharri al-Hadith with ten lines of sanad and friends who only told one, namely Abdullah bin Zaid, so that it can be seen that the hadith is ahad hadith. This hadith in Dhoifkan sheh al-Bani with the reason Isnad Maukuf, (sanad does not continue) and amm bakrim majhul (unknown to the hadith scholars). This is true but partial dhoif, because the same hadith finds authentic results. Thus, leaning and sleeping in a mosque is not an activity that is prohibited in Islamic teachings as long as it does not violate the Islamic rules and doctrines. Keywords: the Law of leaning, Sleep, Mosque